Utilization of Digital Tools in the Classroom Instruction: Student’s Engagement and Academic Performance - Abenez, Judy Ann Tolorio (International Journal of Research in Interdisciplinary Studies, 2025)
This study determines the extent of teachers’ digital-tool utilization and its relationship to student engagement and academic performance in Labuan Central School, Zamboanga City, during School Year 2025–2026. Specifically, it examined teachers’ use of digital tools in pedagogy and assessment, the level of student engagement when such tools are employed, and students’ overall academic performance. It also tested whether significant relationships exist between teachers’ digital utilization and (1) student engagement and (2) academic achievement. The research was conducted in a public elementary school serving a culturally diverse population, including Samal, Subanen, Tausug, and Kalibugan learners. Respondents consisted of thirty-three Grade 4 to Grade 6 public school teachers, chosen because upper-elementary pupils are more capable of responding to technology-based instruction and their teachers more likely to integrate digital tools. A descriptive–correlational design was used to provide a quantitative snapshot of classroom practices and to identify associations between variables without manipulating them. Data were gathered on teachers’ frequency and effectiveness in using digital tools for lesson preparation, online resource gathering, assessment design, and evaluation, as well as on levels of student engagement and academic performance. Findings reveal that teachers “often” employ digital tools in both pedagogy and assessment, while students are likewise “often” engaged when technology is integrated. Student academic performance was found to be satisfactory and consistent. Statistical analysis confirmed significant positive relationships between teachers’ digital-tool utilization and both student engagement and academic performance. These results underscore the value of integrating digital technologies in teaching and assessment to enhance learner participation and achievement.